PENINGKATAN KESADARAN HUKUM SISWA TENTANG BAHAYA PERBUATAN BULLY DI SMP MUHAMMADIYAH 2 PEKANBARU - Raja Desril; Aksar Aksar; Triwahyuni Lestari; Raihana Raihana; Elviandri Elviandri; Desi Somalia Agustina (Jurnal Pengabdian UntukMu NegeRI, 2019)
Bullying behaviour in a school environment can create a less supportive environment for students self-development, bullying behavior can hurt students, so they feel unwanted and rejected by their environment. This will certainly bring effect to the various activities of the students in the school. Causes of bullying due to family factors, environmental factor, school factors and social environmental factors. Bullying is a student who has a physical or social strength that is more appealing to another friend, has a high temperament, and a sense of empathy is low. Victims of bullying often fight against the perpetrators but some of them are subject to the command of the perpetrator and do not dare to fear. To cope with the well-programed bullying, the current countermeasures only include individual approaches by Walikelas, teacher of study field, as well as BK teachers. Keywords: Student law awareness about the dangers of bullying